2011
DOI: 10.1038/mp.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

The neuropathological profile of mild cognitive impairment (MCI): a systematic review

Abstract: Whether mild cognitive impairment (MCI) has a distinct neuropathological profile that reflects an intermediate state between no cognitive impairment and dementia is not clear. Identifying which biological events occur at the earliest stage of progressive disease and which are secondary to the neuropathological process is important for understating pathological pathways and for targeted disease prevention. Many studies have now reported on the neurobiology of this intermediate stage. In this systematic review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 226 publications
(318 reference statements)
3
82
1
7
Order By: Relevance
“…Stephan et al (2011) note that while the latter neural changes are most commonly found in memory-related regions, the hippocampus and the visual association cortex, some studies have also identified neuritic plaques in neocortical regions, and neurofibrillary tangles in the amygdalae. Social cognitive difficulties might therefore not only be a feature of dementia, but also be evident in MCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephan et al (2011) note that while the latter neural changes are most commonly found in memory-related regions, the hippocampus and the visual association cortex, some studies have also identified neuritic plaques in neocortical regions, and neurofibrillary tangles in the amygdalae. Social cognitive difficulties might therefore not only be a feature of dementia, but also be evident in MCI.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to MCI, in a recent systematic review of 162 studies, Stephan et al (2011) noted that MCI is associated with numerous neuropathological changes such as neurochemical deficits, cellular injury, and oxidative stress, in addition to the histopathological hallmarks of AD. Stephan et al (2011) note that while the latter neural changes are most commonly found in memory-related regions, the hippocampus and the visual association cortex, some studies have also identified neuritic plaques in neocortical regions, and neurofibrillary tangles in the amygdalae.…”
Section: Introductionmentioning
confidence: 99%
“…Available data indicate that individuals with MCI have neuropathologic changes in the brain that are intermediate between normal aging and early dementia [33,34]. These findings suggest a transitional state that is evolving to dementia [35].…”
Section: Neurobiologymentioning
confidence: 81%
“…This condition might be associated with early neuropathological aging [5,6], possibly caused by AD, vascular dementia, traumatic brain injuries, metabolic dysregulation, or psychiatric diseases [7,8]. Although individuals with MCI do not yet fulfill the diagnostic criteria for AD/dementia, the high-risk rate of MCI developing to dementia within one year is estimated at about between 10 to 54% [4,[9][10][11][12][13], and that of developing to AD at about 10-15% per year, representing approximately a 10-fold increased risk of AD relative to individuals without memory impairments [4,12].…”
Section: Introductionmentioning
confidence: 99%